Nano conductive filler polymer towards energy efficient EV: A review - Rahman, Mohammed Ataur; Saifullah, Khalid; Sany, Ihsan; Aung, Kyaw Myu; Ismail, Ahmad Faris; Ihsan, Sany Izan (Sila Science, 2018)
Reducing the weight of automobile helps improve energy consumption and reduce greenhouse gas (GHG) emission. Multifunctional components of the automobile are one of the best options which could be useful to make the vehicle lighter and functional as an energy storage and source. Polymer Nano-filler composites signify as the most encouraging and promising family of materials for the solid electrolyte of vehicle energy technology due to its wide band-gap and higher charge density capacity under an electrical field (electron drift) and thermal effect (diffusion). This paper reviews the prospects of Nano-fillers conductive polymer solid electrolyte sandwiched by carbon fibre (CF) and lithium (Li) plate composite for the EV panel serves as the electric energy storing. The reviewed studies shows that the dielectric sandwiched composite body would save 15% electric vehicle energy (3000 Wh) by cutaway body weight and battery size by 30%, store the vehicle regenerative braking power density about 600-700Wh, save the vehicle passengers’ air-conditioning power density about 5% (1000 Wh) from heat insulation. The characteristics of new technology in terms of energy saving and generation indicates that the 33kWh battery equipped electric vehicle would be able to save 4.7 kWh energy which would enhance the vehicle travelling distance about 25 km and reduce the emission and could cut the cost of battery power pack about USD3500 per vehicle.